ALYKUL OSMONOV - A BRIGHT STAR ON A POETIC SKY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article deals with the ideological and stylistic features of the work of thetalented Kyrgyz poet Alykul Osmonov. The author notes the features inherent in the poet’s lyrics:kindness, optimism, love for the Motherland, , service to the high, great love for the nature of thenative land.
Keywords: poet, optimism, love for the Motherland, stylistic features.